Providing Restitution to Children Victims of Pornographic Video Distribution - Riski Mohamad Rasjid; Suwitno Yutye Imran; Nuvazria Achir (Universitas Negeri Gorontalo, 2023)
This study aims to determine the effect of providing restitution on child victims of the distribution of pornographic videos. This research uses empirical legal methods and is based on cases that occur, then analyzed descriptively. The results of the study that the implementation of Restitution of Children as Victims of the Distribution of Pornographic Videos based on Article 7A of the Law of the Republic of Indonesia Number 31 of 2014 concerning the Protection of Witnesses and Victims and PP No. 43 of 2017 concerning the Implementation of Restitution for Children Victims of Criminal Acts. Factors Affecting the Provision of Restitution to Child Victims Distribution of Pornographic Videos, where children and parents or families of both perpetrators and victims do not understand the law, and the existence of Government Regulations (PP) regarding the provision of restitution that must be received by victims. Restitution is certainly not to remove the crime and the process of solving a case. The problem that affects the fulfillment of restitution is also due to the absence of the Witness and Victim Protection Agency so it must wait for the decision and the results of the Central LPSK assessment. In addition, it is also determined by the economic ability and the will of the perpetrator.